RETORIKA TEKSTUAL WACANA NARATIF DALAM BAHASA INDONESIA: UPAYA PENYAMPAIAN PESAN PENGARANG SECARA EFEKTIF Textual Rhetoric of Narrative Discourse Indonesian Language: Efforts to Effectively Convey the Author’s Point) - Sumadi Sumadi (SAWERIGADING, 2009)
The study discusses the textual rhetoric of narrative discourse in Indonesian language, especially those of short stories. It deals with the principles of textual rhetoric covering the processibility, clarity, economy, and expressiveness. In accordance with the four principles in narrative discourse Indonesian of language, can be clarified by the following explanations.The narrative discourse in Indonesian language might have either straight or flashback plot, depending on the authors’ strategy to attract their readers’ interest. The narrative discourse of Indonesian language uses the sentences intended to prevent it from being equivocal. The narrative discourse of Indonesian language is presented briefly without derogating or reducing the message, that is, by deleting, referring, and shortening. The narrative discourse in Indonesian language is constructed in harmony with messages intended for communication using imaginative and metaphorical aspects.